2019
DOI: 10.1016/j.arthro.2018.11.065
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of Alternative Graft Preparations for All-Inside Anterior Cruciate Ligament Reconstruction

Abstract: To biomechanically compare alternative graft constructs for all-inside anterior cruciate ligament (ACL) reconstruction in the event that the semitendinosus harvested is too narrow or too short to make a graft larger than 8 mm. Methods: Bovine extensor tendons were used to make 6 different 9-mm-diameter grafts: traditional 4-strand, anastomosis 4-strand, 6-strand, 3-strand, button-fixation 4-strand, and loopand-tack 4-strand grafts. The grafts were then subjected to cyclic biomechanical testing followed by fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…For this reason, it is evident that early intervention when ACL injury occurs will reduce the probability of additional complications in the other ligaments of the knee. Moreover, as the potential benefits and risks of ACL repair are still largely not well known, it is thereby recommended that regular assessment of the knee joint, especially if injury is suspected, should be performed to allow for early intervention [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is evident that early intervention when ACL injury occurs will reduce the probability of additional complications in the other ligaments of the knee. Moreover, as the potential benefits and risks of ACL repair are still largely not well known, it is thereby recommended that regular assessment of the knee joint, especially if injury is suspected, should be performed to allow for early intervention [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…At times, new surgical techniques are introduced with expanded text and explanation, but inadequate images prevent their reproducibility and clinical use. I am confident that if my harvested hamstring were inadequate, I would be able to successfully build an anastomosis 4-strand, 3-strand, or loop and 4-strand graft from the illustrations provided by Richardson et al 10 Although the illustrations are excellent, the authors deserve more praise for their pragmatic study design in answering a clinically relevant question not often asked. Although many aspects of ACL reconstruction have been extensively studied, I was appreciative of a study that evaluated a "bail-out" technique.…”
Section: See Related Article On Page 1547mentioning
confidence: 95%
“…Traditional 4-strand grafts have good biomechanical properties, but when the tendon length or width is not large enough, other construction methods can also be used to ensure sufficient strength of the graft [60][61][62]. A study showed that anastomosis of 4-strand (699.89 ± 196.73 N), 3-strand (576.20 ± 173.64 N), and loop-and-track 4-strand grafts (769.67 ± 151.89 N) do not biomechanically differ in ultimate force from traditional 4-strand grafts (778.84 ± 176.11 N) [60].…”
Section: Selection and Preparation Of Graftsmentioning
confidence: 99%
“…Traditional 4-strand grafts have good biomechanical properties, but when the tendon length or width is not large enough, other construction methods can also be used to ensure sufficient strength of the graft [60][61][62]. A study showed that anastomosis of 4-strand (699.89 ± 196.73 N), 3-strand (576.20 ± 173.64 N), and loop-and-track 4-strand grafts (769.67 ± 151.89 N) do not biomechanically differ in ultimate force from traditional 4-strand grafts (778.84 ± 176.11 N) [60]. Another biomechanical study on the graft preparation technique by Colter et al [61] also found that a 4-strand single tendon graft was preferred for all-inside reconstruction of the ACL, while the 3-strand single tendon technique was preferred when the tendon length was insufficient, and the 2-strand technique (2 tendons) had a much Cyclic displacement (After preloading and cyclic loading occurred for 500 loading cycles from 50 to 250 N at 1.0 Hz, the final extension length of the graft) than the other groups, so the last technique is not recommended for all-inside reconstruction of the ACL.…”
Section: Selection and Preparation Of Graftsmentioning
confidence: 99%